2022
DOI: 10.1186/s13018-022-03070-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery pathway: association with lower incidence of wound complications and severe hypoalbuminemia in patients undergoing posterior lumbar fusion surgery

Abstract: Background Wound complications are associated with worse satisfaction and additional costs in patients undergoing posterior lumbar fusion (PLF) surgery, and the relationship between enhanced recovery after surgery (ERAS) pathway and wound complications remains poorly characterized. Methods In this retrospective single-center study, we compared 530 patients receiving ERAS pathway care with previous 530 patients in non-ERAS group. The primary aim of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Of these articles, 11 are for fracture-related procedures [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. There are 14 articles on joint replacement-related surgery [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and 15 articles on spine surgery [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The relevant literature search and exclusion process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these articles, 11 are for fracture-related procedures [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. There are 14 articles on joint replacement-related surgery [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and 15 articles on spine surgery [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The relevant literature search and exclusion process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“… ( A ): Risk of bias assessment in studies. ( B ): Risk of bias assessment in each study [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Our ERAS strategy substantially facilitated the early recovery of physiological functions and reduced the incidence of postoperative complications after major spine surgery. Previous studies drew inconsistent conclusions regarding the impact of ERAS protocol on complications after major spine surgery [20]. Porche et al [19]and Dagal et al [17]found no differences between the ERAS and Pre-ERAS groups regarding postoperative complications after spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Balanced postoperative nutrition status relying on adequate enteral intake is important for wound healing. 27,28 Minig et al 29 demonstrated that the traditional diet protocol was associated with a higher wound infection and wound dehiscence rate in patients who underwent gynecologic oncology surgery. Among patients receiving gynecologic oncology surgery with intestinal resection, early-diet protocol still reduced wound infection incidence.…”
Section: Discussionmentioning
confidence: 99%